2019
DOI: 10.1038/s41612-019-0077-5
|View full text |Cite
|
Sign up to set email alerts
|

Recent changes in the South America low-level jet

Abstract: level Jet (SALLJ) is a climatological feature with a critical role in the spatiotemporal distribution of precipitation in South America. While previous studies have focused on the mechanisms and variability of the SALLJ in the central Andes (i.e., southeast Peru, Bolivia, and Paraguay), the occurrence of the low-level jet in the eastern slopes of the northern Andes (i.e., northeast Peru, Colombia, and Venezuela) and its linkages to the central region have not been previously explored. This study shows that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 30 publications
6
51
0
5
Order By: Relevance
“…The SALLJ blows poleward over regions of Bolivia, Paraguay, Southern Brazil, Uruguay and Argentina, where it delivers vast quantities of moisture originated in the Atlantic or over the Amazon basin, feeding severe weather well into subtropical latitudes. From reanalysis data, the SALLJ intensity, frequency (Jones, 2019), and moisture flux (Montini et al, 2019) have shown an increase in the last decades in most of the seasons, affecting precipitation in the eastern Andes. Further studies are needed to understand how these changes will be projected in a warmer climate, which will require improvements in global models to better representing the low-level circulation in the region (Barros and Doyle, 2018).…”
Section: Summary and Open Research Questionsmentioning
confidence: 99%
“…The SALLJ blows poleward over regions of Bolivia, Paraguay, Southern Brazil, Uruguay and Argentina, where it delivers vast quantities of moisture originated in the Atlantic or over the Amazon basin, feeding severe weather well into subtropical latitudes. From reanalysis data, the SALLJ intensity, frequency (Jones, 2019), and moisture flux (Montini et al, 2019) have shown an increase in the last decades in most of the seasons, affecting precipitation in the eastern Andes. Further studies are needed to understand how these changes will be projected in a warmer climate, which will require improvements in global models to better representing the low-level circulation in the region (Barros and Doyle, 2018).…”
Section: Summary and Open Research Questionsmentioning
confidence: 99%
“…However, the ability of models to simulate the preferred locations and mechanisms of water vapor transport is unknown, in part because we do not know what they are in reality (Giannini et al., 2018). In the Andes and Himalayas, areas of similar topographic complexity, the water vapor transports are associated with topographically constrained flows—often through Low‐Level Jets (LLJs) (Acosta & Huber, 2017; Jones, 2019). Models of coarse resolution often struggle to capture the LLJs (Acosta & Huber, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the NASH western ridge controls the location and intensity of the three low‐level jets (LLJs) that play an important role in helping modulate the moisture budgets and precipitation in the central and eastern United States, namely the southerly Great Plains LLJ (GPLLJ; e.g., Higgins et al ., 1997; Doubler et al ., 2015; Wei et al ., 2019), the Caribbean low‐level jet (e.g., Muñoz et al ., 2008), and a third jet feature over the Gulf Stream in the western Atlantic (Zhang et al ., 2006; Colle and Novak, 2010; Helmis et al ., 2013). More recently, the NASH has been shown to affect the northern branch of the South American low‐level jet and precipitation in South America (Jones, 2019). The location and strength of the NASH and the GPLLJ have also been shown to affect surface ozone concentrations and air quality in coastal urban regions along the Gulf of Mexico (Wang et al ., 2016), the trajectory of tropical cyclones (Colbert and Soden, 2012), and the timing of the North and South American monsoons (Arias et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%